Positive Thinking dan Academic Grit pada Siswa SMA di Wilayah Kepulauan Selayar - Destriani Destriani; M. Ahkam Alwi (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
Academic grit is an important psychological factor that enables students to maintain persistence, consistency, and commitment in facing academic challenges. Students in island regions may encounter unique educational barriers, including limited access, fluctuating school engagement, and the risk of dropout, making academic grit particularly relevant to examine. This study aimed to investigate the relationship between positive thinking and academic grit among students at SMA Negeri 6 Selayar. A quantitative approach with a correlational design was employed. The participants consisted of 209 high school students selected using incidental sampling. Data were collected using psychological scales measuring positive thinking and academic grit. Data analysis was conducted using correlation testing to determine the strength and direction of the relationship between the two variables. The results showed a significant positive relationship between positive thinking and academic grit (r = 0.534; p < 0.001). This finding indicates that students with higher levels of positive thinking tend to demonstrate stronger academic grit. Positive thinking may help students interpret academic difficulties more constructively, maintain motivation, and persist in completing learning tasks despite obstacles. The findings highlight the importance of strengthening students’ positive cognitive orientation as part of efforts to enhance academic resilience and persistence. This study provides practical implications for schools, teachers, and guidance and counseling services in developing programs that foster positive thinking, learning motivation, and academic perseverance among high school students, particularly in educational contexts with geographical and social challenges.